Dampak Inflasi terhadap Pola Konsumsi dan Kesejahteraan Mahasiswa: Penelitian - Delima Sianipar; Natasya Ramadhani Citra; Kanaia Caisar; Difany Kaban; Roza Thohiri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to discuss the impact of inflation on the consumption patterns and welfare of university students. Inflation, which is a phenomenon of increasing prices of goods and services in general, has a significant impact on students' ability to fulfill their basic daily needs. In this study, a descriptive quantitative approach was used by distributing questionnaires to 110 students from various majors. The results of this study showed that the majority of students (84.5%) reduced their consumption in response to the increase in prices of goods and services. As many as 68.2% of respondents switched to lower priced products to adjust their spending budget. In addition, inflation also has an impact on students such as anxiety and stress which are included in the psychological aspect, especially for students who live far from outside the city. This study also revealed that 64.4% of students think that government policies have not been effective enough in overcoming inflation and maintaining people's purchasing power. Overall, students need to be wiser and more careful in managing their finances, adapting to economic situations, and finding strategies to deal with economic challenges such as inflation.